PENGARUH LINGKUNGAN DAN PELATIHAN TERHADAP PRODUKTIVITAS DENGAN INTERVENING MOTIVASI PADA PEGAWAI DI BPK JAWA TENGAH - Nurul Hidayah; Pahlawansjah Harahap; Yuli Budiati (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
The aim of this study was to examine the relationship between the work environment and training on work productivity, using work motivation as an intervening variable. This research was quantitative and explanatory, using a questionnaire with several open-ended and closed-ended questions for 162 participants. The SmartPLS approach was used as the technique chosen. The results showed that the work environment had no significant relationship or influence on work productivity, training had a significant influence on work productivity, the work environment had a significant influence or relationship on work motivation, training had a significant relationship with work motivation, and the work environment had a significant relationship with work productivity through the motivation variable. Finally, the training variable had no significant relationship with work productivity when mediated or bridged by the work motivation variable.